Universal Health Coverage (UHC) in the Legal Regulations for Fulfilling Public Health in Indonesia - Amir Burhannudin; Sunny Ummul Firdaus (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
Health services are part of human rights and are bound by applicable legal rules. In an effort to implement these rights, the UN and WHO have initiated the universal health coverage (UHC) program. The UHC program must be implemented by considering the values ​​and benefits to be achieved. This study was conducted to determine the extent of the internalization of legal norms in Universal Health Coverage (UHC) in Indonesia and who is involved in the process.